Enhanced biosorption of transition metals by living Chlorella vulgaris immobilized in Ca-alginate beads - Ahmad, A. (Taylor and Francis Ltd., 2018)
In this study freely suspended and Ca-alginate immobilized C. vulgaris cells were used for the biosorption of Fe(II), Mn(II), and Zn(II) ions, from the aqueous solution. Experimental data showed that biosorption capacity of algal cells was strongly dependent on the operational condition such as pH, initial metal ions concentration, dosages, contact time and temperature. The maximum biosorption of Fe(II) 43.43, Mn(II) 40.98 and Zn(II) 37.43â mg/g was achieved with Ca-alginate immobilized algal cells at optimum pH of 6.0, algal cells dosage 0.6â g/L, and contact time of 450â min at room temperature. The biosorption efficiency of freely suspended and immobilized C. vulgaris cells for heavy metals removal from the industrial wastewater was validated. Modeling of biosorption kinetics showed good agreements with pseudo-second-order. Langmuir and DâR isotherm models exhibited the best fit of experimental data. The thermodynamic parameters (ÎGÂ°, ÎHÂ°, and ÎSÂ°) revealed that the biosorption of considered metal ions was feasible, spontaneous and exothermic at 25â45Â°C. The SEM showed porous morphology which greatly helps in the biosorption of heavy metals. The Fourier transform infrared spectrophotometer (FTIR) and X-rays Photon Spectroscopy (XPS) data spectra indicated that the functional groups predominately involved in the biosorption were CâN, âOH, COOâ, âCH, C=C, C=S and âCâ. These results shows that immobilized algal cells in alginate beads could potentially enhance the biosorption of considered metal ions than freely suspended cells. Furthermore, the biosorbent has significantly removed heavy metals from industrial wastewater at the optimized condition. Â© 2018 Informa UK Limited, trading as Taylor & Francis Group